A new amynodontid from the Eocene of South China and phylogeny of Amynodontidae (Perissodactyla: Rhinocerotoidea). (2nd November 2017) - Averianov, Alexander; Danilov, Igor; Jin, Jianhua; Wang, Yingyong
Abstract : Cadurcodon maomingensis sp. nov. is described based on a partial skull and associated vertebrae from the middle–upper Eocene Youganwo Formation in the Maoming Basin, Guangdong Province, China. The taxonomy of Cadurcodon Kretzoi, 1942 ( = Sianodon Xu, 1965, syn. nov.; = Paracadurcodon Xu, 1966, syn. nov.) is revised, and a new diagnosis of the genus is provided. It includes six species: C. ardynensis (Osborn, 1923), C. kazakademius Biryukov, 1961, C. bahoensis (Xu, 1965) comb. nov., C. suhaituensis (Xu, 1966) comb. nov., C. houldjinensis B.-Y. Wang, Qiu, Zhang, Wu, & Ning, 2009 and C. maomingensis sp. nov. A new phylogenetic hypothesis of Amynodontidae is based on the cladistic analysis of the distribution of 48 characters in 16 amynodontid taxa. The family is divided into two sister taxa, Metamynodontini ( Paramynodon, Megalamynodon and Metamynodon ) and Cadurcodontini ( Procadurcodon, Zaisanamynodon, Cadurcodon and Cadurcotherium ). The remaining amynodontid genera are considered incertae sedis . The evolution of amynodontids was confined mainly to Central and East Asia, with four dispersal events to North America ( Amynodon, Amynodontopsis, Metamynodontini and Procadurcodon ), and one to Europe and South Asia ( Cadurcotherium ). The holotype of C. maomingensis sp. nov. is an adult male with body mass estimated as 1.4 tons. Amynodontids show considerable increase in size during evolution, with the largest species weighing over two tons ( C. kazakademius, Zaisanamynodon borisovi and Procadurcodon orientalis ). http://zoobank.org/urn:lsid:zoobank.org:pub: FD6EEE3E-AE06-4DA2-AFFD-39362724C1C2